Analysis of The Elementary School Teachers’ Ability to Use Technology on The Mathematics Online Learning - Faizah, Hanim; Sugandi, Eko (Universitas Islam Negeri Raden Intan Lampung, 2022)
In Indonesia, the implementation of online mathematics learning does not always run smoothly, there are various obstacles that occur, such as the lack of gadgets owned by teachers or students, internet networks are still weak, etc. So that the readiness of mathematics teachers in managing online learning is very necessary, especially in utilizing technology. Thus, it is necessary to analyze the readiness of mathematics teachers in carrying out online learning. In this study, we aim to describe (1) online mathematics learning in primary schools during the COVID-19 pandemic; (2) the ability of elementary school teachers to use technology during online learning, especially in learning mathematics; and (3) the content that teachers use to present online learning. We conducted research by distributing an online survey to 56 primary school teachers, over a period of approximately two weeks of data collection. The findings in this study are that most mathematics teachers in schools still use whatsApp and google meet or zoom media in conducting online learning, elementary school teachers still have not mastered learning technology well, and most teachers are still limited to using video downloads from YouTube, PPT and conventional books to present learning.